414 Competitive Advantage: An Analysis of Matched and Unmatched United States Neurological Surgery Residency Applicants From 2009-2021. (April 2023) - Goldman, Liam; Iyer, Ankitha Mahesh; Barpujari, Awinita; Rogers, James Louis; Reddy, Vamsi; Johnson, Jeremiah N.
Abstract : INTRODUCTION: National Resident Matching Program releases a detailed report of residency match statistics for each specialty. Securing a training position in a United States neurological surgery residency program is notoriously competitive, and the subspecialty has long maintained a match rate much lower than other specialties. There remains a paucity of recently studied longitudinal trends in academic and extracurricular characteristics of successfully matched neurological surgery residency applicants. METHODS: Residency applicant self-reported data, obtained from the American Association of Medical Colleges Electronic Residency Application Service, were collected from yearly "Results and Data: Main Residency Match" (2009-2021) and biennial "Charting Outcomes in the Match" (2009-2020) National Residency Match Program summary reports. RESULTS: From 2009-2021, the number of neurological surgery residency programs and positions increased from 97 to 115 and 191 to 234, respectively. Matched applicants' average United States Medical Licensing Exam (USMLE) Step 1 scores significantly increased (239 to 248; p = 0.01332), while average USMLE Step 2 Clinical Knowledge scores rose (237 to 252; p = 0.05682) during the study period. Average number of distinct research experiences among matched applicants increased (3.3 to 6.1; p = 0.5398), while the average number of abstracts, presentations, and publications increased from 7.8 to 23.4 (p = 0.0746). Lastly, Alpha Omega Alpha (AOA) membership (p = 0.00077) and percentage graduating from a top National Institutes of Health-funded medical school (p = 0.00396) significantly differed between matched and unmatched neurological surgery residency applicants. CONCLUSIONS: Matched neurological surgery residency applicants had significantly fewer average number of distinct specialties ranked, higher USMLE Step 1 scores, greater AOA membership, and more frequently graduated from top 40 NIH-funded medical schools than their unmatched counterparts. Additional research considering applicant-level intersectional data is warranted to further understand the match process.